Curcumin's Dose-Dependent Attenuation of Gastric Cancer Cell Progression Via the PI3K Pathway Blockade - Gen Xi; Qingtao Dong; Bo Yang; Desheng Jiao; Shahanavaj Khan (SAGE Publishing, 2023)
Background: Gastric cancer stands as a primary cause of cancer-related deaths worldwide, making the discovery of new therapeutic agents essential for enhancing treatment outcomes. Curcumin, a polyphenolic compound found in turmeric ( Curcuma longa ), has demonstrated potential in multiple cancer types due to its anti-cancer characteristics. This research aimed to examine the impact of curcumin on gastric cancer cell growth, migration, and invasion, as well as its influence on the phosphoinositide 3-kinase (PI3K) signaling cascade. Methods: Gastric cancer cell lines were exposed to varying curcumin concentrations, followed by assessments of cell viability, migration, and invasion. Furthermore, gene and protein expression levels associated with the PI3K signaling cascade were evaluated using reverse transcription-polymerase chain reaction (RT-PCR) and Western blot analysis. Results: The findings revealed a dose-dependent decrease in cell viability, migration, and invasion in gastric cancer cells treated with curcumin. Additionally, curcumin administration led to the downregulation of key genes and proteins within the PI3K signaling process, such as PI3K, Akt, and mTOR. Conclusion: These findings propose that curcumin may exercise its anti-cancer effects on gastric cancer cells, partly by suppressing the PI3K signaling pathway. This study's outcomes support curcumin's potential as a therapeutic agent for gastric cancer and encourage further exploration of its underlying molecular mechanisms and in vivo effectiveness.